Effects of Gamification in BCI Functional Rehabilitation - de Castro-Cros, Martí; Sebastian-Romagosa, Marc; Rodríguez-Serrano, Javier; Opisso, Eloy; Ochoa, Manel; Ortner, Rupert; Guger, Christoph; Tost, Dani (Frontiers in Neuroscience, 2020)
Objective To evaluate whether introducing gamification in BCI rehabilitation of the upper limbs of post-stroke patients has a positive impact on their experience without altering their efficacy in creating motor mental images (MI). Design A game was designed purposely adapted to the pace and goals of an established BCI-rehabilitation protocol. Rehabilitation was based on a double feedback: functional electrostimulation and animation of a virtual avatar of the patient’s limbs. The game introduced a narrative on top of this visual feedback with an external goal to achieve (protecting bits of cheese from a rat character). A pilot study was performed with 10 patients and a control group of six volunteers. Two rehabilitation sessions were done, each made up of one stage of calibration and two training stages, some stages with the game and others without. The accuracy of the classification computed was taken as a measure to compare the efficacy of MI. Users’ opinions were gathered through a questionnaire. No potentially identifiable human images or data are presented in this study. Results The gamified rehabilitation presented in the pilot study does not impact on the efficacy of MI, but it improves users experience making it more fun. Conclusion These preliminary results are encouraging to continue investigating how game narratives can be introduced in BCI rehabilitation to make it more gratifying and engaging.